Dikotomi Kendali dalam Perspektif Stoikisme dalam Islam: Studi Komparatif pemikiran Henry Manampiring dan Fahruddin Faiz - Yuti Alpiah; Fathurohim (La-Tahzan: Jurnal Pendidikan Islam, 2026)
This research aims to analyze the concept of the "Dichotomy of Control" in Stoicism through a comparative study of Henry Manampiring's thoughts in the book "Filosofi Teras" and Fahruddin Faiz's thoughts via the "Ngaji Filsafat" channel. The increasing phenomenon of anxiety disorders in the modern era has made Stoicism a popular alternative for emotional management in Indonesia. However, the application of this secular philosophy in Muslim society requires a theological review. This study employs a qualitative method with library research. The results indicate that Manampiring positions the Dichotomy of Control as a horizontal-rational emotional management tool to achieve ataraxia (mental resilience). Meanwhile, Fahruddin Faiz spiritualizes the concept by integrating it into Sufism values, where the dichotomy of control is seen as a synchronization between Ikhtiar (effort) and Tawakkal (trust in God) to achieve tuma’ninah (inner peace). This research formulates a "Theological Dichotomy of Control" model as a synthesis that unites Western rationality with Islamic spirituality, providing a foundation for Muslim society to face modern life dynamics while remaining grounded in the concepts of Qada and Qadar.